Spatially resolved denitrification coupled with methane and arsenite oxidation at the millimeter-scale straw–soil interface - Xin-Di Zhao; Ya-Qin Wang; Sha Zhang; Jia-Qi Li; Yu-Jia Cai; Xiao Shu; Zheng Chen; Si-Yu Zhang (Proceedings of the National Academy of Sciences, 2026)
Straw return reshapes the biogeochemical processes in paddy soils by driving microbial transformation of key elements. Despite growing awareness of these individual processes, the integration of these processes under millimeter-scale spatiotemporal heterogeneity remains unclear. Combining high-resolution geochemical profiling with multiomics, we revealed that straw addition altered the depth-dependent dynamics of arsenic, carbon, and nitrogen, establishing a sophisticated three-layer microbial stratification. We identified 1) an 18 mm organic matter (OM)-rich layer extending from the straw layer, which serves as a methanogenic epicenter co-occurring with active nitrogen fixation microbes; 2) an overlying layer dominated by aerobic methane oxidation and denitrification microbes; and 3) a deeper substraw layer dominated by anaerobic arsenite oxidation and denitrification microbes. Significantly positively correlated abundances of transcribed mcrA with nifH genes and pmoA or aioA / arxA with denitrification genes were identified. Corroboratively, intensified co-occurrence patterns of mcrA with nifH , pmoA with denitrification, and aioA / arxA with denitrification genes were observed in the OM-rich, upper, and lower layers, respectively. Moreover, the co-occurred mcrA - nifH and aioA - nirS / arxA - narG genes in different metagenome-assembled genomes presented 80.6 to 260.8- and 1.55 to 6.85-fold greater transcriptional activity in the OM-rich and lower layers than in the other layers, respectively. Our results demonstrated that straw incorporation established a dynamic soil redox zone, restructuring millimeter-scale microbial networks and promoting potentially coupled denitrification with arsenite or methane oxidation, as well as methanogenesis with nitrogen fixation. These findings provide a mechanistic basis for optimizing subsurface straw placement and nitrate application to enhance nutrient cycling and mitigate environmental risks.